Promoter engineering‐mediated Tuning of esterase and transaminase expression for the chemoenzymatic synthesis of sitagliptin phosphate at the kilogram‐scale. Issue 8 (21st May 2021) - Khobragade, Taresh P.; Yu, Seongseon; Jung, Hyunsang; Patil, Mahesh D.; Sarak, Sharad; Pagar, Amol D.; Jeon, Hyunwoo; Lee, Somin; Giri, Pritam; Kim, Geon‐Hee; Cho, Sung‐Su; Park, Seong‐Hwa; et al.
Abstract: Here, we report a bienzymatic cascade to produce β‐amino acids as an intermediate for the synthesis of the leading oral antidiabetic drug, sitagliptin. A whole‐cell biotransformation using recombinant Escherichia coli coexpressing a esterase and transaminase were developed, wherein the desired expression level of each enzyme was achieved by promotor engineering. The small‐scale reactions (30 ml) performed under optimized conditions at varying amounts of substrate (100–300 mM) resulted in excellent conversions of 82%–95% for the desired product. Finally, a kilogram‐scale enzymatic reaction (250 mM substrate, 220 L) was carried out to produce β‐amino acid (229 mM). Sitagliptin phosphate was chemically synthesized from β‐amino acids with 82% yield and > 99% purity. Abstract : A promoter engineering strategy was successfully applied for selective control of the expression level of each enzyme. The kilogram scale reaction (14.31 kg) was performed with 92% conversion (11.66 kg) and >99 e.e . The applicability of this study was demonstrated for synthesis of leading oral antidiabetic drug, sitagliptin.